Image of a city - Comparison of Bratislava and Prague - Šišková, Dominika (2017)
This master thesis deals with the importance of the destination image in general as well as with the image of the two selected cities, Bratislava and Prague. The goal of this thesis was to provide a sufficient evidence in order to identify the city with the better perceived image among tourists. In order to reach the ultimate goal, a field research targeting tourists who visited both cities at least once, was conducted. The results of the survey indicated that destination image of the two cities was influenced by the prior visitation and country of residence. In addition, the findings revealed that the perceived image of Prague is more positive than the image of Bratislava.